"I don't know what I was expecting": Home visits by neonatology fellows for infants discharged from the NICU. Issue 4 (22nd August 2017) - Hobbs, Janice E.; Tschudy, Megan M.; Hussey‐Gardner, Brenda; Jennings, Jacky M.; Boss, Renee D.
Abstract: Background: When families transition from the neonatal intensive care unit (NICU) to the home, they become responsible for their infant's daily medical needs. Though neonatology physicians prepare families for hospital discharge, it is unclear how much clinicians understand about how their teaching and instructions translate into home care. The goal of this study was to evaluate the influence of a home visiting program on neonatology fellows' understanding of family needs soon after hospital discharge. Methods: Neonatology fellows conducted a home visit for an infant recently discharged. Before the visit, fellows reviewed their original discharge instructions, along with information about the family's neighborhood. During the home visit, fellows reviewed their discharge planning with families and discussed any challenges experienced. Afterwards, fellows completed a semi‐structured interview; these transcriptions were manually coded for themes. Results: Fellows identified several common women/family discharge challenges. These challenges fall into four domains: (1) inadequate discharge preparation, (2) medicalization of the home, (3) family adjustment to new "normal, " and (4) the relevance of social context to discharge planning. Most (90%) fellows reported the home visit experience would affect their future NICU discharge practices and all agreed that home visits should be a part of neonatology training. Conclusions: Home visits allowed neonatology fellows to examine how their discharge preparation did, or did not, meet the family's needs. Incorporating home visits into neonatology training could help fellows learn about the relevance of social and community factors that are difficult to assess in the inpatient setting.